Barbus anatolicus, a new barbel from the Kızılırmak and Yeşilırmak River drainages in northern Anatolia (Teleostei: Cyprinidae) - Turan, Davut; Kaya, Cüneyt; Geiger, Matthias; Freyhof, Jörg (Zootaxa, 2018)
Barbus anatolicus, new species, is described from the Kızılırmak and Yeşilırmak River drainages in the southern Black Sea basin. It is distinguished from other Barbus species in the Middle East by having 58–71 total lateral line scales, a moderately ossified last simple dorsal-fin ray, serrated along about 70–80% of its posterior margin, many small irregular shaped black or brown spots, smaller or as large as scales, often forming large, dark-brown blotches on the head, back and flank in adults and juveniles, and a concave posterior dorsal-fin margin. In addition, DNA barcode data reject the hypothesis that it belongs to one of the other species of the B. barbus species group. Barbus bergi from Bulgaria and adjacent Turkey is treated as synonym of B. tauricus. Barbus tauricus was previously believed to be restricted to the Crimean Peninsula but is found to be widespread in the Black Sea basin.